Communication during the Prophet Muhammad's Time: Media, Methods, and its Relevance in the Modern Era - Nofrianti, Mami; Avinash, Buschhaus; Wang, Yuanyuan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This article discusses the communication practices implemented by Prophet Muhammad (SAW), focusing on the media and methods used in spreading the message of Islam. Through an analysis of historical context, the article illustrates how the Prophet optimized various communication channels, including oral communication, letters, and direct interaction, to reach diverse communities. Additionally, the study highlights the relevance of the Prophet's communication principles in the modern context, where information technology and social media have become primary tools for disseminating information. By examining the values of effective, honest, and inclusive communication taught by the Prophet, the article offers a fresh perspective on how contemporary society can leverage these approaches to enhance communication in various aspects of life.